Implementation of Career Guidance Services for Senior High School in Determining Major at College Level - Saiful Akhyar Lubis; Abdurrahman Abdurrahman; Rahmi Yasirna (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
The purpose of this study was to determine the preparation of student career guidance services, the implementation of student career guidance services, and the supporting and inhibiting factors of student career guidance services at Al-Azhar High School Medan. This study uses a qualitative method with descriptive type that is to describe the object of research as itself. Data sources are school principals, guidance and counseling teacher, and Al-Azhar Plus High School students in Medan. The results showed that: (1) Preparation of career guidance services in class XII students at Al-Azhar Plus High School Medan in determining majors to lecture levels through the first, the existence of a checklist of problems (DCM) that is used to determine the extent to which students have confusion about his career goals. Second, through testing the scholastic aptitude test (TBS). From the results of this test students also know the results of the test and know their abilities. (2) The form of implementing career guidance services through three programs are; First: information services, second: information gathering visits at various tertiary institutions, third: group or individual discussions.